Law Enforcement in Parking Lot Levy Collection Cases at Indomaret and Alfamart - Lestari, Ayuni Dwi (Proceedings Series on Social Sciences & Humanities, 2023)
His research is motivated by the phenomenon that occurs in parking which as a whole is known that parking in Indomaret and Alfamart minimarkets is parking that is free of charge. However, people who should not pay for parking services must pay. This can cause losses to the community because in this case the community becomes uncomfortable shopping at the minimarket due to illegal parking collection. The purpose of writing is to find out and analyze the collection of parking fees at Indomaret and Alfamart according to the Regional Regulation of Banyumas Regency Number 8 of 2008 concerning Parking Fees on Public Roads and to find out the efforts of local governments in regulating the collection of parking fees in Banyumas Regency. Questions that arise in compiling this research, namely 1. Is the collection of parking fees at Indomaret and Alfamart in accordance with the Regional Regulation of Banyumas Regency Number 8 of 2008 concerning Parking Fees on Public Roads? What are the local government's efforts to regulate the collection of parking fees in Banyumas Regency? This study uses empirical juridical research methods. The results of this study are not in accordance with what was expected.